The impact of genetic variants in the CYP2C8 gene on bladder cancer susceptibility - Qu, Weixing; Zhang, Fuzhou; Cheng, Yongyi; Li, Jing; Zhou, Jiancheng (Frontiers in Endocrinology, 2022)
Background: Bladder cancer is the most common leading cause of mortality around worldwide. Previous studies have been indicated that genetic factors are significantly associated with bladder cancer progression. For instance, the CYP2C8 gene is involved in bladder cancer progression. However, little is known about the impact of CYP2C8 genetic polymorphisms on bladder cancer risk. We aimed to detect the association between CYP2C8 variations and bladder cancer susceptibility. Methods: This study included 550 healthy subjects and 217 bladder cancer patients. The odds ratios (ORs) and 95 % confidence intervals (CIs) were calculated to determine the correlation of CYP2C8 polymorphisms with bladder cancer risk. Multifactor dimensionality reduction (MDR) was carried out to investigate the influence of SNP-SNP interactions on bladder cancer. Results: Our study showed that two SNPs were significantly associated with an increased risk of bladder cancer (rs1934951: OR 1.96, 95% CI 1.37-2.82, p = 2.67E-04; rs17110453: OR 1.89, 95% CI 1.35-2.67, p = 2.53E-04). On the contrary, two SNPs identified in the study had protective effects on bladder cancer (rs1934953: OR 0.26, 95% CI 0.14-0.47, p = 1.20E-05; rs2275620: OR 0.40, 95% CI 0.21-0.76, p = 0.005). MDR analysis suggested that the combination of rs1934953, rs1934951, rs2275620, and rs17110453 was the best model to predict bladder cancer (CVC 10/10, testing accuracy 0.6720, p < 0.0001). Conclusion: There was a significant association between CYP2C8 polymorphisms (rs1934953, rs1934951, rs2275620, and rs17110453) and susceptibility to bladder cancer.